A STUDI KEPEMIMPINAN KEPALA DESA DALAM MENINGKATKAN PARTISIPASI MASYARAKAT DI DESA PEGAT BUKUR KECAMATAN SAMBALIUNG KABUPATEN BERAU - Barkah, Shandy (ECO-BUILD, 2017)
Village Head's leadership in promoting community participation by Direct Approach The direct approach undertaken by the village head by reviewing directly in the field intended to ascertain whether local residents really do activities together. In addition, it is also to see if an error occurs in the activities and provide guidance in the event of an error in the implementation of activities. On the Indirect Approach village chief in this case is the approach that is carried out indirectly through the reports of citizens to hold monitoring to see and assess the extent of community activities if there is a shortage would be used as learning materials in order to be better in the future. The purpose of this study is to determine how the village head's leadership in improving public participation, where this research is qualitative research and data sources obtained from informants, documents and research. Data was collected through interviews, observation and documentation. In the leadership of the village head directly observed activities of mutual cooperation undertaken by the villagers and then provide guidance to the public in accordance with any activity undertaken, in addition to reviewing directly village chief also asked the residents or the village secretary to report any activity undertaken community Pegat grain in the village when the village head was unable to attend the event.